Observation of aerosol particle capturing behavior near gas-liquid interface - Shinichiro UESAWA (The Japan Society of Mechanical Engineers, 2020)
An aerosol particle capturing by a gas-liquid interface has been applied in many industries. One example of this is the radioactive aerosol removal system in the safety system of the nuclear reactor such as filtered venting system. In this study, to clarify the capturing behavior of aerosol particles by the gas-liquid interface, we developed a direct observation technique of the aerosol particle behavior and have been performing the observation experiment of the aerosol particle capturing behavior near the gas-liquid interface. In the experiment, we observed the aerosol particle capturing behavior on the gas-liquid interface of a single droplet. The capturing behavior of the aerosol particles near the droplet interface was observed by using a high-speed and high-resolution video camera and a fiber light. In this observation, we confirmed that aerosol particles were captured at the gas-liquid interface of the droplet after the velocity of the aerosol particles decreases near the droplet. On the other hand, some aerosol particles closing to the droplet did not reach the interface and were not captured. In comparison between the behavior and Stokes number, particles with higher Stokes number were easy to be captured at the gas-liquid interface. Especially, particles with much higher Stokes number penetrated through the gas-liquid interface and were captured inside the droplet. This capturing behavior was not considered in previous studies because the capturing behavior of a “solid” single fiber applied to the capturing behavior of aerosol particles with a droplet. Thus, this study made clear that Stokes number affects capturing behavior. In addition, we confirmed both soluble and insoluble particles in water also were captured in a droplet in high Stokes number. This result means that particles can be captured in a droplet in high Stokes number even if aerosol particles are insoluble in water.